Directed evolution of novel adeno-associated viral vectors for gene therapy - Schaffer, David (Henry Stewart Talks, 2014)
Recent successes in gene therapy, Problems in the field with naturally derived vectors, Directed evolution as an approach to engineer optimal viral vector variants that meet clinical needs, Examples: development of variants to evade neutralizing antibodies and evolution for enhanced delivery in the retina
Archived at 2023/07/31